2009
DOI: 10.1021/la902994r
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Alkaline Metal Cations with Oxidic Surfaces: Effect on the Morphology of SnO2Nanoparticles

Abstract: Reaction pathways to SnO(2) nanomaterials through the hydrolysis of hydrated tin tetrachloride precursors were investigated. The products were prepared solvothermally starting from hydrated tin tetrachloride and various (e.g., alkali) hydroxides. The influence of the precursor base on the final morphology of the nanomaterials was studied. X-ray powder diffraction (XRD) data indicated the formation of rutile-type SnO(2). Transmission electron microscopy (TEM) studies revealed different morphologies that were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
(32 reference statements)
2
20
0
Order By: Relevance
“…No remarkable shift and no characteristic peaks for impurity, such as SnO, ZnSnO 3 , and Zn 2 SnO 4 in diffraction peak were detected. The surface energies of SnO 2 follow the trend (110) < (100) < (101) < (001), indicate the c-axis to be the preferential growth direction [20].…”
Section: Resultsmentioning
confidence: 84%
“…No remarkable shift and no characteristic peaks for impurity, such as SnO, ZnSnO 3 , and Zn 2 SnO 4 in diffraction peak were detected. The surface energies of SnO 2 follow the trend (110) < (100) < (101) < (001), indicate the c-axis to be the preferential growth direction [20].…”
Section: Resultsmentioning
confidence: 84%
“…Besides, the cations (Na + vs NH 4 + ) may also contribute to the different PL properties of NaF-and NH 4 F-mediated cryogels. Molecular dynamics simulations showed that the adsorption energy of Na + cations on the SnO 2 crystal faces is larger than that of NH 4 + , resulting in the preferential anisotropic one-dimensional growth in the presence of Na + ions [33]. Similarly, the possible high adsorption energy of Na + cations upon the europium fluoride complex may dilute the optically active ions in the cryogel host matrix, as usually a high concentration of optically active ions leads to a nonradiative decay (concentration quenching) [13].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, for Ni:SnO 2 nanorods, as shown in Figure 3(d), the lattice fringe were found to be ~0.336 nm and ~0.331 nm, which were assigned to plane (110) tetragonal rutile indicating that the preferential growth direction was [001]. 26 Likewise, lattice spaces for Pd:SnO 2 , shown in Figure 3( 27 Also, the peaks of Sn 2+ 3d 5/2 and Sn 2+ 3d 3/2 were detected in Pd:SnO 2 samples, suggesting that Sn 4+ ions were partially reduced to Sn 2+ during the doping process. This observation is similar to a previous study by Aragón et al 20 On the other hand, the region of O 1s in Pd:SnO 2 could be de-convoluted into three different oxygen peaks.…”
Section: Compositional and Morphological Analysismentioning
confidence: 99%